Marangoni Driven Boundary Layer Flow of Carbon Nanotubes Toward a Riga Plate - Shafiq, Anum; Zari, Islam; Khan, Ilyas; Khan, Tahir Saeed; Seikh, Asiful H.; Sherif, El-Sayed M. (Frontiers in Physics, 2020)
The objective of this article is to explore the radiative marangoni boundary layer flow on the existence of carbon nanotubes through a surface embedded is an electromagnetic actuator defined as a riga plate. To judge the performance of Lorentz forces on the bases of nanoparticles temperature fluxes, two different types of carbon nanotubes, namely single wall carbon nanotube and multi wall carbon nanotubes saturated into water used as base fluid. With the introduction of some viable dimensionless variables into the system of nonlinear partial differential equations, the resulting nonlinear designed flow of marangoni boundary layer flow over riga plate is developed. The proposed schemes of governing equations are then converted into ordinary differential equations by similarity transformation. To sort out characteristics of thermal radiation and effect of Hartmann number through marangoni boundary layer flow of nanofluid, some suitable boundary conditions are utilized. The solution of indicated governing equations and for the convergence of control parameters, one of best analytical method is utilized. The velocity and temperature profiles of various parameters are deliberated in detail for numerical significance. Numerical survey of embedded parameters is then depicted on graphs and tables. Finally, some accomplished comments are also our part of consultation.